Guilty Pleasure? Communicating Sexually Explicit Content on Dating Apps and Disillusionment with App Usage. (6th December 2019) - Niehuis, Sylvia; Reifman, Alan; Weiser, Dana A; Punyanunt-Carter, Narissra M; Flora, Jeanne; Arias, Vladimir S; Oldham, C Rebecca
Abstract: Some people send or receive sexually explicit images or messages when using dating apps. Seeing unwanted content may produce adverse effects, consistent with expectancy violations theory (EVT), and disillusion some users. To test links between encountering sexually explicit materials and dating app disillusionment (with oneself, with others, and regret over app usage), we surveyed two samples of dating app users. Study 1 ( n = 531 college students) focused on Tinder, whereas Study 2 ( n = 209 Mechanical Turk workers) examined dating apps broadly. In each study, a latent class analysis sorted users into four groups, based on their dating app engagement with sexual content. Participants who rarely exchanged and did not enjoy sexual content were most regretful, as even one bad experience might have violated their expectations. Contrary to EVT, participants with high enjoyment of explicit materials felt disillusioned with themselves. Participants citing relationship-seeking purposes for app usage were highly disillusioned when heavily involved with explicit content.